The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000107047
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maternal Dietary Docosahexaenoic Acid Intake on Rat Pup Myelin and the Auditory Startle Response

Abstract: We investigated the effects of maternal docosahexanoic acid (DHA) supplementation on pups’ auditory startle responses and the composition of brain myelin. Methods: Timed-pregnant rats were fed throughout pregnancy and lactation diets that contained 0, 0.3, 0.7 or 3% of total fatty acids as DHA. Milk was collected from culled pups’ stomachs on postnatal day (PND) 3, latency of the auditory startle reflex was measured on PND 15, and pups were killed and brains collected on PND 24. Results: Higher levels of DHA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…More testing at time points later in life could provide more information on the full potency of LCPUFA. It has been reported that high levels of n-3 PUFA were associated with a negative effect on neural development by prolonging auditory brain stem conduction times and a delay in auditory startle reflex in rodents [77,78]. These studies show the importance of dosage but indirectly also stress the relevance of the n-6/n-3 ratio, which deserves further attention.…”
Section: Discussionmentioning
confidence: 69%
“…More testing at time points later in life could provide more information on the full potency of LCPUFA. It has been reported that high levels of n-3 PUFA were associated with a negative effect on neural development by prolonging auditory brain stem conduction times and a delay in auditory startle reflex in rodents [77,78]. These studies show the importance of dosage but indirectly also stress the relevance of the n-6/n-3 ratio, which deserves further attention.…”
Section: Discussionmentioning
confidence: 69%
“…Although studies show that there is postnatal accretion of nervonic acid in sphingomyelin, there are no systematic reports assessing the effect of a DHA-rich diet on myelination [ 6 , 49 ]. Interestingly, a diet high in DHA results in longer latencies of the auditory startle response (a functional indicator of myelination) [ 50 ]. In contrast to MUFA such as nervonic acid, PUFA content in myelin phospholipids is low, consisting of 1/6 to 1/3 of the PUFA content of gray matter phospholipid [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…When patients with Zellweger syndrome (who have very low levels of DHA in the brain, retina, and other tissues) received DHA supplementation, MR imaging showed increases in myelination (Martinez, 2001). When pregnant rat dams were fed a DHA-supplemented diet, higher levels of DHA in the maternal diet affected the lipid composition in the offsprings’ myelin (Haubner et al, 2007). Cheatham et al also suggest that DHA may affect the formation of memory by facilitating the function of the NMDA channels (Nishikawa, Kimura, & Akaike, 1994) and affecting hippocampal neurotransmission (Itokazu, Ikegaya, & Nishikawa, 2000); the hippocampus and frontal regions are fundamental for attentional control, memory, and higher-level cognitive processes.…”
Section: Discussionmentioning
confidence: 99%